Comprehensive study on cooling effectiveness and thermoelectric conversion of a novel helium/hydrogen-based closed Brayton cooling system for a hydrogen aero-engine - Qiurui Xin; Xiaohui Bai; Helong Jin; Chengao Duan; Yuxi Li; Cunliang Liu (Case Studies in Thermal Engineering)
The Brayton cycle and thermoelectric generators offer significant potential for cooling hydrogen aero-engines. However, existing research on Brayton cooling schemes integrated with thermoelectric generators (TEGs) remains limited, typically relying on assumed state parameters that are challenging to obtain. This study proposes a one-dimensional method that considers the coupling relationships between the mainstream, TEGs, and coolant, thereby investigating the cooling and thermoelectric conversion processes of aero-engines under real operating conditions. Subsequently, four cooling schemes—direct cooling (DC), Brayton cooling (BC), direct thermoelectric cooling (DTC), and Brayton thermoelectric cooling (BTC)—are analyzed. Consequently, the DC provides the best cooling performance, with the highest wall temperature of hot components below 750 K. The BC generates the highest mechanical power, reaching 124.7 kW. Furthermore, the utilization of TEGs reduces the cooling efficiency but increases the total power output of the schemes. Compared to the DC, the maximum wall temperature of the DTC increases by 496.3 K, while the thermoelectric power is the greatest, reaching 116.6 kW. The maximum wall temperature of the BTC rises by 335.5 K compared to the BC, whereas its total power output is the highest, at 142.3 kW. This study guides the cooling and waste heat utilization in hydrogen aero-engines.